Efficiency of Organizations Entitled to Award Academic Degrees - Sergey I. Pakhomov; Igor M. Matskevich; Valery A. Gurtov; Natalia V. Melekh; Ekaterina I. Zaugolnikova (National Research Mordova State University, 2020)
Introduction. As part of the Bologna process since September 1, 2016, the Russian government has granted the right to award academic degrees to leading educational and scientific organizations on par with Dissertation Defense Councils under Higher Attestation Commission, modeled after the system adopted at OECD member-states and universities. Currently, 27 educational and scientific organizations are exercising this right. However, the problematic issue is the assessment of their efficiency. The purpose of this research is to analyze the efficiency of Dissertation Councils of the above-mentioned scientific and educational organizations by comparing them in terms of efficiency with classical Dissertation Defense Councils established by the decree of the Ministry of Education and Scie nce of Russia. Materials and Methods. The research objects are Dissertation Councils of scientific and educational organizations of higher education (hereinafter referred to as pilot organizations) that have the right of independent award of academic degrees according to the Federal Law No. 148 issued on May 23, 2016 "On Amendments to Article 4 of the Federal Law 'On research and state scientific and technological policy'". Dissertation Councils efficiency analysis is made using following indicators: Dissertation Councils members' compliance with the Higher Attestation Commission requirements, structure of candidate and doctoral defenses, Dissertation Councils members' publications and publication activity of degree seekers. Statistical data analysis methods were applied including mean comparison me thods, clustering, factor analysis. Results. There are 337 pilot Dissertation Defense Councils and 374 classical Dissertation Defense Councils. In 2016, 24% of defenses were reviewed by pilot councils of the total number of defenses in classical Dissertation Councils of the entire network. In 2018 70 doctoral and 591 candidate defenses in "pilot" councils were held, amounting to 7% of the total number of defe nses in classical Dissertation Councils. Discussion and Conclusion. The article will be useful to the heads of federal authorities making management decisions in the field of training and certification of highly qualified scientific personnel, to the chairmen and scientific secretaries of dissertation councils, as well as to scientific and pedagogical workers carrying out analytical studies in this subject area.